Latent Transforming Growth Factor-β Binding Protein-2 Regulates Lung Fibroblast-to-Myofibroblast Differentiation in Pulmonary Fibrosis via NF-κB Signaling - Zou, Menglin; Zou, Jingfeng; Hu, Xingxing; Zheng, Weishuai; Zhang, Mingyang; Cheng, Zhenshun (Frontiers in Pharmacology, 2021)
Despite past extensive studies, the mechanisms underlying pulmonary fibrosis (PF) still remain poorly understood. The aberrantly activated lung myofibroblasts, predominantly emerging through fibroblast-to-myofibroblast differentiation, are considered to be the key cells in PF, resulting in excessive accumulation of extracellular matrix (ECM). Latent transforming growth factor-β (TGFβ) binding protein-2 (LTBP2) has been suggested as playing a critical role in modulating the structural integrity of the ECM. However, its function in PF remains unclear. Here, we demonstrated that lungs originating from different types of patients with PF, including idiopathic PF and rheumatoid arthritis-associated interstitial lung disease, and from mice following bleomycin (BLM)-induced PF were characterized by increased LTBP2 expression in activated lung fibroblasts/myofibroblasts. Moreover, serum LTBP2 was also elevated in patients with COVID-19-related PF. LTBP2 silencing by lentiviral shRNA transfection protected against BLM-induced PF and suppressed fibroblast-to-myofibroblast differentiation in vivo and in vitro. More importantly, LTBP2 overexpression was able to induce differentiation of lung fibroblasts to myofibroblasts in vitro, even in the absence of TGFβ1. By further mechanistic analysis, we demonstrated that LTBP2 silencing prevented fibroblast-to-myofibroblast differentiation and subsequent PF by suppressing the phosphorylation and nuclear translocation of NF-κB signaling. LTBP2 overexpression-induced fibroblast-to-myofibroblast differentiation depended on the activation of NF-κB signaling in vitro. Therefore, our data indicate that intervention to silence LTBP2 may represent a promising therapy for PF.